THE PHOTOELECTROCHEMICAL REDUCTION OF P-BROMO-NITROBENZENE - AN ECEE, ECE OR DISP PROCESS - MECHANISTIC RESOLUTION VIA CHANNEL ELECTRODE VOLTAMMETRY - Compton, R; Dryfe, R (1994)
The photoelectrochemical reduction of p-bromo-nitrobenzene in acetonitrile solution, containing tetrabutylammonium perchlorate as supporting electrolyte, was studied using a platinum channel electrode. It is shown that p-bromo-nitrobenzene is reduced at a half-wave potential of -0.98 V (vs. Ag pseudo-reference electrode) to form a radical anion which is stable in the absence of light. On irradiation with light of wavelength 330 nm, corresponding to an absorption band in the radical anion, appreciable photocurrents flow and in situ electrochemical electron spin resonance (ESR) shows the formation of the nitrobenzene radical onion. The mechanism of formation is shown to occur via a "photo-ECE" mechanism rather than either "photo-ECEE" or "photo-DISP" processes by means of (i) the variation in photocurrent with flow rate, and (ii) novel phototransient experiments in which the photocurrent is followed after the step-wise application of light to the system after steady-state transport l imited currents have been established in the dark at various flow rates. Experiments conducted in the presence of different concentrations of added Br- show steady-state photocurrents that are diminished relative to those flowing under corresponding conditions in the absence of added Br-. The kinetic modelling of this effect is consistent with a light-induced breakage of the carbon-bromine bond in the C-step of the ECE process followed by reaction of the ·φNO2 radical thus formed with both Br- and the solvent system. © 1994.